Elevated CK-MB levels are associated with adverse clinical outcomes in acute pancreatitis: a propensity score-matched study - Jiang, Xiao-Ting; Ding, Ling; Huang, Xin; Lei, Yu-Peng; Ke, Hua-Jing; Xiong, Hui-Fang; Luo, Ling-Yu; He, Wen-Hua; Xia, Liang; Lu, Nong-Hua; Zhu, Yin (Frontiers in Medicine, 2023)
Cardiac injury, reflected by the measured concentrations of chemicals released from injured cardiac muscle, is common in acute pancreatitis (AP). However, there is no adequate evidence assessing the impact of cardiac injury on AP-related outcomes.Creatin kinase-Myocardial Band (CK-MB) mainly exists in the myocardium.Therefore, we sought to evaluate the relationship between the increase in CK-MB and adverse clinical outcomes of AP.This propensity score-matched study analyzed AP patients admitted to the Department of Gastroenterology in the First Affiliated Hospital of Nanchang University from June 2017 to July 2022. Propensity score matching and multivariate logistic regression analysis were used to explore the relationship between CK-MB elevation and AP outcome variables.A total of 5944 patients were screened for eligibility; 4802 were ultimately enrolled. Overall, 896 (18.66%) of AP patients had elevated (>24 U/mL) CK-MB levels; 895 (99.89%) were paired with controls by propensity score matching. The propensity score-matched cohort analysis demonstrated that mortality (OR, 5.87; 95% CI, 3.89-8.84; P<0.001), severe acute pancreatitis (SAP) (OR, 2.74; 95% CI, 2.23-3.35; P<0.001) and infected necrotizing pancreatitis (INP) (OR, 3.40; 95% CI, 2.34-4.94; P<0.001) were more frequent in the elevated CK-MB (>24 U/mL) group than in the normal CK-MB (≤ 24 U/mL) group. By the multivariate logistic regression analysis, elevated CK-MB levels were independently associated with increased mortality (OR, 2.753, 95% CI, 2.095-3.617, P<0.001), SAP incidence (OR, 2.223, CI, 1.870-2.643, P<0.001), and INP incidence (OR, 1.913, 95% CI, 1.467-2.494, P<0.001). CK-MB elevation was an independent risk factor for adverse clinical outcomes in AP patients. Conclusion: CK-MB elevation was significantly related to adverse outcomes in AP patients, which makes it a potentially useful laboratory parameter for predicting adverse clinical outcomes of AP.